2006
DOI: 10.1152/ajplung.00189.2005
|View full text |Cite
|
Sign up to set email alerts
|

Integrins β1, α6, and α3contribute to mechanical strain-induced differentiation of fetal lung type II epithelial cells via distinct mechanisms

Abstract: -Mechanical forces regulate lung maturation in the fetus by promoting type II epithelial differentiation. However, the cell surface receptors that transduce these mechanical cues into cellular responses remain largely unknown. When distal lung type II epithelial cells isolated from embryonic day 19 rat fetuses were cultured on flexible plates coated with laminin, fibronectin, vitronectin, collagen, or elastin and exposed to a level of mechanical strain (5%) similar to that observed in utero, transmembrane sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…The PAEC were propagated in MEM containing 10% FBS and sodium pyruvate. Alveolar type II epithelial cells were isolated from lungs of fetal C57BL/6 mice (embryonic days 17-18), as previously described (49). Briefly, after collagenase digestion, cell suspensions were sequentially filtered through 100-, 30-, and 15-m nylon meshes using screen cups (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The PAEC were propagated in MEM containing 10% FBS and sodium pyruvate. Alveolar type II epithelial cells were isolated from lungs of fetal C57BL/6 mice (embryonic days 17-18), as previously described (49). Briefly, after collagenase digestion, cell suspensions were sequentially filtered through 100-, 30-, and 15-m nylon meshes using screen cups (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a vaginal plug was considered as day 0.5 of pregnancy. Type II cells were isolated as previously described (42). Briefly, after collagenase digestion, cell suspensions were sequentially filtered through 100-, 30-, and 15-m nylon meshes using screen cups (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have confirmed that integrins play a central role in mechanotransduction in virtually all cell and tissue types (39 -41). Previous experiments from our laboratory have shown that specific integrin subtypes contribute to mechanical strain-induced differentiation of fetal type II epithelial cells (42).…”
mentioning
confidence: 90%
“…Fetal rat lungs were obtained from timed-pregnant Sprague-Dawley rats (Charles Rivers, Wilmington, MA) and E19 type II cells were isolated as previously described (6). Epithelial cells were then seeded onto Bioflex plates precoated with collagen-1 (Flexcell Corporation, Hillsborough, NC) and maintained in serum-free Dulbecco's modified Eagle's medium (DMEM) for 24 h. Plates containing adherent cells were mounted in a Flexercell FX-4000 Strain Unit (Flexcell Corp.).…”
Section: Methodsmentioning
confidence: 99%